2011
DOI: 10.1007/s00442-011-2092-z
|View full text |Cite|
|
Sign up to set email alerts
|

Absence of snow cover reduces understory plant cover and alters plant community composition in boreal forests

Abstract: Snow regimes affect biogeochemistry of boreal ecosystems and are altered by climate change. The effects on plant communities, however, are largely unexplored despite their influence on relevant processes. Here, the impact of snow cover on understory community composition and below-ground production in a boreal Picea abies forest was investigated using a long-term (8-year) snow cover manipulation experiment consisting of the treatments: snow removal, increased insulation (styrofoam pellets), and control. The sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 66 publications
2
101
1
Order By: Relevance
“…Wind transport of snow is expected to be greatly reduced in a warmer winter (as happened in this region in 2010), when wetter snowfall and more frequent icing occur, implying that snow distribution patterns could become more uniform at higher elevations under a warmer climate. More uniformity in snow distribution patterns could influence plant communities by favouring the establishment of individuals in exposed areas that would previously have been relatively snow-free throughout the winter and by potentially shifting away from species that benefited from longlasting snow-cover in depressions or snow berms (Kreyling et al, 2012). Recent temperature increases, as drivers of snow pattern change as well as possible soil moisture deficits, are expected to have contrasting effects on the trajectories of plant communities (Crimmins et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Wind transport of snow is expected to be greatly reduced in a warmer winter (as happened in this region in 2010), when wetter snowfall and more frequent icing occur, implying that snow distribution patterns could become more uniform at higher elevations under a warmer climate. More uniformity in snow distribution patterns could influence plant communities by favouring the establishment of individuals in exposed areas that would previously have been relatively snow-free throughout the winter and by potentially shifting away from species that benefited from longlasting snow-cover in depressions or snow berms (Kreyling et al, 2012). Recent temperature increases, as drivers of snow pattern change as well as possible soil moisture deficits, are expected to have contrasting effects on the trajectories of plant communities (Crimmins et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the study demonstrates that both bryophytes and vascular plants at boreal mires exhibit a time lag of more than five years in response to nitrogen and temperature rise. The slow and gradual shift from Kreyling et al (2012) showed in an experiment conducted in a boreal Picea abies forest that understory species composition was strongly altered by snow cover manipulations and vegetation cover, in particular the dominant dwarf shrub Vaccinium myrtillus (bilberry) and the most abundant mosses, significantly declined in the snow removal treatment. As a conclusion, shifts are caused in vegetation by frost damage as well.…”
Section: Scandinaviamentioning
confidence: 99%
“…V. myrtillus cover was positively correlated with precipitation and longitude (geographic location). Both factors may reflect the important influence of climate and microclimate on this species as reported in boreal and high mountain forests (Löffler 2007;Rasmus et al 2011;Kreyling et al 2012). For instance, the greatest annual precipitation was found in the Atalaiador and Vila sites, which also showed the greatest covers of V. myrtillus and mosses in the study area, and a high floristic similarity among both sites.…”
Section: Discussionmentioning
confidence: 86%